To be a military sniper - Mast, Gregory; Halberstad, Hans (Zenith Press, 2007)
Aside from nerves of steel, pinpoint precise targeting skills, and uncanny adaptability, what does it take to be a military sniper? This book lays out the details of training and traits of character that make for success in one of the most challenging and mysterious jobs the military has to offer.Author Gregory Mast, who has commanded both a rifle and a heavy machine-gun platoon, offers a clear account of what its like to be a sniper, required to stay in one position for days at a time, calling upon extensive training in camouflage and concealment, stalking and observation, precision marksmanship in a variety of operational conditions, and all those skills that, along with aptitude, turn a trainee into the deadliest of marksman